Organismo, pedagogía y empatía: observaciones en torno a Machado de Silviano Santiago - Fernando Bogado (Cuadernos LIRICO)
Based on the reading of Machado (2016) by Silviano Santiago, this article aims to review the construction of an “I researcher” that would function as central to deploy the project initiated by the author in Em liberdade (1981) and characterized as a deconstruction of the biographical genre. The guiding question of our investigation is the specific type of relationship that Santiago establishes with Machado de Assis in this novel, making this investigation/narrative a slow movement from deconstruction towards Gadamerian hermeneutics and, even, pedagogy. Therefore, the novel (romance) results in a work close to the autonomous register of literature due to its appeal to the organism and the corporeal discourse, which would put into discussion the critical approaches in vogue in the 21 st century around the non-specificity or hybridity of literary discourses.